Role of layered structure in ductility improvement of layered Ti-Al metal composite. (July 2018) - Huang, Meng; Xu, Chao; Fan, Guohua; Maawad, Emad; Gan, Weimin; Geng, Lin; Lin, Fengxiang; Tang, Guangze; Wu, Hao; Du, Yan; Li, Danyang; Miao, Kesong; et al.
Abstract: Layered Ti-Al metal composite (LMC) was designed and fabricated by hot-rolling and annealing of pure Ti and Al sheets. The as-prepared composite exhibits high tensile ductility, being superior to any individual Ti or Al sheets. The stress/strain evolution and fracture behavior of the LMC were analyzed by in-situ observations during the tensile deformation. Three deformation stages of LMC were clearly observed by neutron diffraction: elastic stage, elastic-plastic stage and plastic stage. It is found that stress partitioning at the elastic-plastic deformation stage improves the strain balance of LMC, but leads to an internal stress accumulated at the interface. Additionally, a strain-transfer from Ti to adjacent Al layers relieves the strain localization of Ti layers in LMC, which improves the ductility of Ti. Both stress partitioning and strain localization of Ti layers facilitate the nucleation of cracks at a low macro strain. However, the crack propagation is constrained by layered structure. In terms of the Al layers, the constrained micro-cracks relieve the stress concentration in Al layer and improve the ductility of Al layers, so that cracking indirectly affects the plastic deformation behavior of LMC, then improving its entire ductility. This work provides a new structural strategy towards simultaneously improving strength and ductility to develop high performance LMC by structural design. Graphical abstract: Image 1